Implementasi IoT pada Alat Pendeteksi Kesuburan Tanah Menggunakan Algoritma Fuzzy Logic - Dimas Firmansyah; Ida Bagus Gede Dwidasmara (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
So far, farmers have been able to determine soil fertility using manual methods. Farmers only look at the soil directly without measuring the level of moisture and nutrients contained in their plots of land. Due to farmers' lack of knowledge in determining the level of soil fertility on their land plots, they need a tool to help their performance. Later, this soil fertility tool will determine the level of humidity, temperature, and pH in the soil. With this tool, it is hoped that farmers will be able to optimize their harvests.